Analisis Keputusan Minat Berkunjung Kembali Wisatawan Saloka Theme Park - Nisa Rahmi Dalimunthe; Evi Yulia Purwanti (Universitas Diponegoro, 2021)
Semarang Regency has a variety of attractions, one of them is Saloka Theme Park which is located in Gumuksari, Lopait. Saloka has 25 main attractions and animation laser show entertainment, Klinthing Baru. This research aims to review and analyza tourist demand for Saloka tourism objects. This study uses 100 sample questionnaires that distributed online with accidental sapling, namely the technique sample determine based on chance, anyone who accidentally meets with a researcher can be used as a sample if deemed suitable as a data source. Data samples were processed using logistic regression analysis and descriptive analysis. The logistics analysis test is used to describe the relationship between the dependent variable and the independent variable, while descriptive analysis i s used to describe profil of respondents. Dependent variable used is interest of revisiting, while the independent variables are income per month, age, group visits, facilities, vahicles and the price of admission. The result showed that income per month, age, and vehicle had a significant effect, while the group visit, facility variable and entrance ticket price had no significant effect. Variable income, facilities, ride and ticket prices have a positive effect, while age and group visits have a negative effect. Based on observations showing that various kinds of games and entertainment rides are outdoors.